Recent Advances in Breathable Barrier Membranes for Individual Protective Equipment - A. Brewer, Stuart (Recent Patents on Materials Science, 2011)
This review covers patents that have been published recently on materials that can be incorporated into garments to provide protection from toxic chemicals. Toxic chemicals are defined as substances that can either kill or seriously incapacitate people due to the physiological effects that they have. The review specifically concentrates on semipermeable membranes i.e. those that will act as a barrier to toxic materials but are permeable to water vapour. These breathable membranes offer a lower physiological burden than completely impermeable barrier films since they will allow for significant amounts of water vapour to escape through the protective clothing. These membranes, that in this review are defined as those that possess water vapour permeabilities in excess of 400g m-2 day-1, can be divided into porous and non-porous (hydrophilic) systems. In addition, recent advances in responsive (adaptive) membranes that can switch between permeable and non-permeable modes are also discussed.
Keywords: poly-(2-acryl-amido-2-methyl propane sulphonic acid)